Field Tests to Investigate the Penetration Rate of Piles Driven by Vibratory Installation - Zhaohui Qin; Longzhu Chen; Chunyu Song; Lei Sun (Shock and Vibration)
Factors directly affecting the penetration rate of piles installed by vibratory driving technique are summarized and classified into seven aspects which are driving force, resistance, vibratory amplitude, energy consumption, speeding up at the beginning, pile plumbness keeping, and slowing down at the end, from the mechanism and engineering practice of the vibratory pile driving. In order to find out how these factors affect the penetration rate of the pile in three major actors of vibratory pile driving: (i) the pile to be driven, (ii) the selected driving system, and (iii) the imposed soil conditions, field tests on steel sheet piles driven by vibratory driving technique in different soil conditions are conducted. The penetration rates of three different sheet pile types having up to four different lengths installed using two different vibratory driving systems are documented. Piles with different lengths and types driven with or without clutch have different penetration rates. The working parameters of vibratory hammer, such as driving force and vibratory amplitude, have great influences on the penetration rate of the pile, especially at the later stages of the sinking process. Penetration rate of piles driven in different soil conditions is uniform because of the different penetration resistance including shaft friction and toe resistance.